The origin of feces : what excrement tells us about evolution, ecology, and a sustainable society - Waltner-Toews, David, 1948- (ECW Press, 2013)
An entertaining and enlightening exploration of why waste matters, this cultural history explores an often ignored subject matter and makes a compelling argument for a deeper understanding of human and animal waste. Approaching the subject from a variety of perspectives--evolutionary, ecological, and cultural--this examination shows how integral excrement is to biodiversity, agriculture, public health, food production and distribution, and global ecosystems. From primordial ooze, dung beetles, bug frass, cat scats, and flush toilets to global trade, pandemics, and energy, this is the awesome, troubled, uncensored story of feces.